PENINGKATAN PRODUKTIVITAS TERNAK MELALUI PENGGUNAAN FEED SUPPLEMENT UREA MOLASES BLOCK PADA TERNAK RUMINANSIA: REVIEW - Roselin Gultom; Beatus Gregorio Randiman Lagur; Katharina Chantika Idim Nguru; Petrus Canisius Dario Tangi (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Feed plays a crucial role in the global food industry, and it is the largest and most important production component, ensuring safe, plentiful, and affordable animal-based protein. The main challenge to livestock development in developing countries is the scarcity and fluctuations in the quality and quantity of feed supplies throughout the year. The use of feed supplements, in the form of Urea Molasses Block (UMB), to provide nitrogen, minerals, and vitamins that are lacking in fibrous feed offers several benefits, including convenience, storable, and usable, as well as lower risks compared to other methods. Supplementing Urea Molasses Block creates beneficial conditions in the rumen, thereby increasing the digestibility of fibrous animal feed. Giving Urea Molasses Block (UMB) to ruminant livestock has a positive impact on dry matter intake, rumen microbes, body weight gain, milk production, and reproductive performance in ruminants..